1992
DOI: 10.1007/bf00130509
|View full text |Cite
|
Sign up to set email alerts
|

Perifusion system: its use in the study of the neuroendocrine control of human pituitary tumoral cells

Abstract: Regulation of hormone release involves both long term and short term controls, which depends upon which receptor is activated (nuclear or membrane) and upon which stimulating agent is used. When long term regulation is involved, protein synthesis is the major event determining the observed changes in hormone release. When short term regulation is involved, membrane transducing mechanisms are implicated and variations in ion fluxes, adenylate cyclase, phospholipase C, D or A2 activities are immediately followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1995
1995
1996
1996

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…Although unresponsiveness to TRH has been reported in cultured prolactinomas (27), TRH stimulated in vitro PRL secretion of all the adenomas that we studied in perifusion in the present study, as shown already (28). This result is consistent with the presence of specific TRH receptors in the large majority of prolactinomas (29) and demonstrates the functional activity of the perifused cells.…”
Section: Discussionsupporting
confidence: 94%
“…Although unresponsiveness to TRH has been reported in cultured prolactinomas (27), TRH stimulated in vitro PRL secretion of all the adenomas that we studied in perifusion in the present study, as shown already (28). This result is consistent with the presence of specific TRH receptors in the large majority of prolactinomas (29) and demonstrates the functional activity of the perifused cells.…”
Section: Discussionsupporting
confidence: 94%